Scratch hardness of glass - Sawamura, Shigeki; Wondraczek, Lothar (Physical Review Materials, 2018)
Since Mohs devised his prominent scale for mineral classification, the scratching behavior of inorganic solids has been intuitively related to material hardness. However, lateral deformation testing by instrumented indentation reveals a large variability in the resistance to scratch deformation relative to hardness, caused by the extent to which scratching requires higher work of deformation at given hardness due to material pileup and friction. Across a broad variety of glassy materials (with covalent, ionic, and metallic bonding), there is a strong correlation between scratch hardness and bulk modulus. Other than in crystalline materials, however, the spatial distribution of bond energy is heterogeneous on a molecular scale, so that no simple correlation exists with the mean-field average of bond energy density. Instead, inherent heterogeneity in the spatial distribution of bond energy and associated fluctuations in rigidity on a superstructural scale suggest an analogy between glasses and granular media.
CRIS-Team Scopus Importer:2023-04-20